Communications in the Social Security Administrations as Part of the Measures of Corporate Social Responsibility in their Activity Optimization - Пандурска, Ралица (Научни трудове, 2020)
Nowadays corporate social responsibility takes an important role in companies’ and institutions’ management. From an occasional activity and an act of employers’ goodwill, now it is becoming a social image etalon. The levels and forms of its implementation become more diverse, including the field of social security.The goal of the current research is to present the good practices in the active and effective communication of the social security administrations, as being main part of the corporate social responsibility in these institutions. These guides could be useful to the persons who need help and want to be informed on their social rights and responsibilities and to all other interested parties of the social security process.As a result of the research is expected to prove the thesis that the social security administrations should implement CSR policies and practices in their activities that would increase the trust in the institutions and in the social security system at all and would improve administrations` capacity.This features and guidelines could as well be adapted and implemented in other institutions in order to expand their implementation in the practice.